Effect of Methotrexate Drug on Some Parameters of Kidney in Newborn mice - Kh. Hussain, Zainab; AL-Mhdawi, Ferial; AL-Bakri, Nahla (Iraqi Journal of Science, 2023)
Thirty pregnant albino mice with average body weight of 25-30gm and 8-14 weeks old were used to investigate the toxicity of the oral administration of anticancer methotrexate on kidneys after birth. Pregnant were received (single dose) of drug at different days of gestation and were divided into three groups (10mice / group), control groups were administered distilled water, the two remaining groups were administered by 2.5 and 7.5 mg/kg body weight of methotrexate. The changes in kidneys of newborns revealed significant (p<0.05) decrease in kidneys weights, kidneys lengths, pelvises lengths, and glomeruli diameters. The increase in concentration of methotrexate has increasing significant effect on kidneys of embryo and newborns.